Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2012 - Casas-Sánchez, José Miguel (Northwest Atlantic Fisheries Organization (NAFO), 2012)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 26th to July 24th 2012. The area surveyed was extended up to depths of 800 fathoms (1450 meters) following the same procedures as in previous years. This year a total of 174 valid hauls were made by the vessel R/V Vizconde de Eza with the usual survey gear (Lofoten), 118 up to 730 meters depth. The surveyed area has properly prospected the 32 strata planned. The general indexes for shrimp were estimated taken into account the traditional swept area (strata 1-19, up to depths of 730 m.) and the total area surveyed (strata 1-34, up to depths of 1450 m.). As in 2010 and 2011 the strata 26 and 27sited in the southeast of the bank with depths from 600 to 800 fathoms (1100-1400 m.) will not be surveyed due to the presence in the bottoms of great quantities of mud and sponges. The results concerning shrimp are presented and compared to those from previous years of the same series. The biomass and abundance in 2012 decreased from 2011 (36 % and 39% respectively), and they were the lowest values in the EU survey series. Also, as in previous years (2004-2011) the youngest specimens (age 1) didn’t appear in the catches, and they were weakly presents in the small mesh size bag attached to the cod-end of the main gear, suggesting the absence of any strong year classes since 2003. As previous years, the sharp decline of shrimp biomass in Flemish Cap was associated with a strong increase of the cod stock.